(untitled) (INMR - Innovation & Management Review, 2017)
The low-income market has become the focus of many companies since the economic growth of emerging countries has been highlighted nationally and internationally. Thus, the development of innovations for this segment has also become a central issue in academia and management. Literature on disruptive innovation presents assumptions that justify its analysis in light of the low-income market. Thus, this article analyzes the concept of disruptive innovation in this market. For this purpose, the article is divided into two parts: the first focuses on a theoretical review of disruptive innovation, whilst the second presents a review of national publications dealing with this concept. The national literature review shows that few studies have been concerned with addressing these concepts in Business Administration and Marketing, especially considering aspects of the low-income context.